1981
DOI: 10.1063/1.441408
|View full text |Cite
|
Sign up to set email alerts
|

Rate constants for deactivation of N2(A) v′=0,1 by O2

Abstract: The removal of N2(A 3Σu+, v′=0,1) by O2 has been studied in a room temperature discharge-flow apparatus by monitoring the temporal decay of the 0,6 and 1,10 bands of the Vegard–Kaplan system. Rate constants for the reaction with O2 are (2.3±0.4) and (4.1±0.7)×10−12 cm3 molecule−1 s−1 for v′=0 and 1, respectively. The rate constant measured for v′=0 is about 35% lower than commonly accepted values for the rate constant for quenching N2(A) by O2. This discrepancy is shown to result from the fact that most other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…The simulation of vibrational populations of electronically excited N2 and O2 molecules in the middle atmosphere of the Earth… 151 with the constant of the interaction k4d=1.0•10 -12 cm 3 s -1 . The calculated total constant k4=2.1•10 -12 cm 3 s -1 for the processes (4a-4d) is in good agreement with experimental data (1.9±0.3)•10 -12 cm 3 s -1 [Dreyer et al, 1974], (2.3±0.4)•10 -12 cm 3 s -1 [Piper et al, 1981] and (2.5±0.4)•10 -12 cm 3 s -1 [Thomas and Kaufman, 1985]. In the case of the interaction of vibrationally excited metastable nitrogen N2(A 3 Σu + ,v'>0) with O2 molecules there is the transfer of electronic energy on the excitation of repulsive states with the production of two oxygen atoms [Kirillov, , 2011.…”
Section: N2(supporting
confidence: 85%
“…The simulation of vibrational populations of electronically excited N2 and O2 molecules in the middle atmosphere of the Earth… 151 with the constant of the interaction k4d=1.0•10 -12 cm 3 s -1 . The calculated total constant k4=2.1•10 -12 cm 3 s -1 for the processes (4a-4d) is in good agreement with experimental data (1.9±0.3)•10 -12 cm 3 s -1 [Dreyer et al, 1974], (2.3±0.4)•10 -12 cm 3 s -1 [Piper et al, 1981] and (2.5±0.4)•10 -12 cm 3 s -1 [Thomas and Kaufman, 1985]. In the case of the interaction of vibrationally excited metastable nitrogen N2(A 3 Σu + ,v'>0) with O2 molecules there is the transfer of electronic energy on the excitation of repulsive states with the production of two oxygen atoms [Kirillov, , 2011.…”
Section: N2(supporting
confidence: 85%
“…A summary of these measurements is presented in Table 1. Three investigations, [13][14][15] which have provided V-level specific bimolecular rate constants, k V′ 's, for the reaction N 2 (A 3 Σ u + ,0 e V′ e 3) + O( 3 P) are in good agreement.…”
Section: Introductionmentioning
confidence: 82%
“…The fraction of the reaction that proceeds via the + O( 3 P) reaction path under pseudo-first-order conditions is given by and similarly the fraction of the reaction that proceeds via the + path is given by where f v is the fractional vibrational level population of the and k v and K v are the vibrational level specific bimolecular rate constants for the quenchers O( 3 P) and O 2 , respectively. The f v 's were determined experimentally 26 and numerically. , An average of the vibrational level specific k v 's and K v 's reported in the literature was used in the calculation for v‘ ≤ 6 and v‘ ≤ 3, respectively. ,,,,, For K v 's 4 ≤ v ≤ 6, the bimolecular rate constants were estimated using the power law dependence of K , i.e., K v ∝ v n . Under the experimental conditions used in the present investigation processes (i) and (ii) accounted for ∼60% of the removal of the initial in the reaction + O( 3 P), leaving ∼40% for reaction with O( 3 P).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an N 2 q-0 2 rate coefficient is ---2 orders of magnitude larger than that for quenching of a'(v = 0) to the ground (X) state [Piper, 1987], and laboratory measurements by Katayama et al [1994] have clearly shown that N 2 + N 2 collisions transfer energy within the singlet system. Furthermore, based on N2(A) + O collisional rate coefficients [Piper et al, 1981;Thomas and Kaufman, 1985] the N 2 q-O rate coefficient is an order of magnitude larger than that for N 2 q-0 2. Given the density of the atmosphere at ---105 km (n(N2) • 4 x 10 •2 cm -3, n(O2) • 9 x 10 TM cm -3, and n(O) • 3.5 x 10 • cm -3 [Hedin, 1987]) collisional processes would give a transition rate of •2000 s-•.…”
Section: N2(a •Iig) + M • N2(a' •-) + Mmentioning
confidence: 89%